Implementing smart bus stand to reduce local transportation risks for passengers in Dhaka city - Khan, Md. Asif Imran; Kawlam, Salamun; Nayeem, Md Jannatul; Quadir, Rezwan UL (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.